2005
DOI: 10.1253/circj.69.890
|View full text |Cite
|
Sign up to set email alerts
|

Serial Changes in Circulating Concentrations of Soluble CD40 Ligand and C-Reactive Protein in Patients With Unstable Angina Undergoing Coronary Stenting Role of Inflammatory Mediators in Predicting Late Restenosis

Abstract: Background This study tested the hypothesis that serum concentrations of high-sensitivity C-reactive protein (hs-CRP) and soluble CD40 ligand (sCD40L) significantly reflect serial changes in patients with unstable angina, and thus the serum concentrations of these inflammatory biomarkers may be good candidates for predicting late restenosis after coronary stenting. Methods and ResultsThe circulating concentrations of sCD40L and hs-CRP were prospectively measured (both pre-procedure, and on days 21, 90, and 180… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 39 publications
3
28
1
Order By: Relevance
“…These 2 inflammatory biomarkers reflect the fact that the study patients had an ongoing inflammatory process. Therefore, our findings are consistent with recent studies 6,7,12,18,19) and further support the finding that CRP, an index of inflammation, has a proatherosclerotic effect and promotes the atherosclerotic process. 4,10,16,[18][19][20] One of the important findings of this study was that the circulating level of hs-CRP rapidly and significantly declined on day 30 following the procedure.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These 2 inflammatory biomarkers reflect the fact that the study patients had an ongoing inflammatory process. Therefore, our findings are consistent with recent studies 6,7,12,18,19) and further support the finding that CRP, an index of inflammation, has a proatherosclerotic effect and promotes the atherosclerotic process. 4,10,16,[18][19][20] One of the important findings of this study was that the circulating level of hs-CRP rapidly and significantly declined on day 30 following the procedure.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, these findings further support those obtained by recent studies. 7,12) The most important finding in this study was that levels of hs-CRP and total cholesterol increased significantly 3 months after withdrawing the atorvastatin therapy. Therefore, these findings expand upon those in previous and recent studies 7,12,13) and encourage the continuous use of statin therapy for high-risk patient subgroups for primary or secondary prevention.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Numerous studies have shown that inflammatory biomarkers play a pivotal role in the risk stratification and prediction of clinical outcomes in patients with acute coronary syndrome [1][2][3][4][5] . Immunohistochemical staining of atherosclerotic lesions further demonstrates Yung-Lung Chen and Tzu-Hsien Tsai contributed equally to this work.…”
Section: Introductionmentioning
confidence: 99%